2019
DOI: 10.1002/chem.201900896
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of Vincadifformine Enabled by a Thiourea‐Phosphonium Salt Catalyzed Mannich‐Type Reaction

Abstract: An asymmetric total synthesis of vincadifformine is described. The limited tactics with chiral cation‐directed catalysis in total synthesis inspired the development of our strategy for accessing this alkaloid in enantionrich form. The route features a thiourea–phosphonium salt catalyzed Mannich‐type reaction, a phosphine‐promoted aza‐Morita–Baylis–Hillman reaction and a trifluoroacetic acid promoted deprotection/amidation cascade process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…After extensive modification of the catalyst structure, the thiourea‐phosphonium salt catalyst 13 was found to be the best catalyst for the asymmetric Mannich‐type reaction of N ‐Boc indole aldimine 14 with dimethyl ethylmalonate 15 (Scheme 5). [13] The product 16 was obtained in 92% yield with 84% ee.…”
Section: C−c Bond‐forming Reactions: Mannich Strecker and Friedel‐cmentioning
confidence: 96%
See 1 more Smart Citation
“…After extensive modification of the catalyst structure, the thiourea‐phosphonium salt catalyst 13 was found to be the best catalyst for the asymmetric Mannich‐type reaction of N ‐Boc indole aldimine 14 with dimethyl ethylmalonate 15 (Scheme 5). [13] The product 16 was obtained in 92% yield with 84% ee.…”
Section: C−c Bond‐forming Reactions: Mannich Strecker and Friedel‐cmentioning
confidence: 96%
“…This review covers the various applications of phosphonium salts as Lewis acid catalysts under homogeneous conditions, as well as asymmetric phase‐transfer catalysts, reported since 2017. It focuses on the application of phosphonium salts (especially amino acid‐derived and dipeptide‐based bifunctional phosphonium salts developed by Zhao [11] and Wang [12] ) in various reactions, such as the Mannich, Strecker and Friedel‐Crafts reactions for the formation of C−C bonds, and annulation reactions, as well as in the total synthesis of bioactive molecules such as vincadifformine [13] . The synthesis of phosphonium salts will not be discussed in detail in this review.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, asymmetric phase-transfer catalysis (PTC) has been recognized as a straightforward and efficient tool for the enantioselective synthesis of chiral compounds. , A survey of literature disclosed that the research groups of Maruoka, Ooi, and Ma made key breakthroughs in asymmetric PTC involving monofunctional phosphonium salts as catalysts. The groups of Zhao and Lu pioneered the development of several bifunctional phosphonium salt catalysts from amino acids, and achieved some asymmetric addition and substitution reactions. Very recently, our group developed asymmetric aza-Darzens cyclization and formal [4 + 1] annulation reactions by employing a dipeptide-based chiral phosphonium salt as a phase-transfer catalyst, and suggested that the stereocontrol might be realized by the synergistic effect of H-bonding and ion pair interactions offered by such bifunctional phosphonium catalysts. , Inspired by these results, we speculated that such highly tunable bifunctional phosphonium salts may result in a practical asymmetric multicomponent reaction protocol for constructing structurally spiro pyrrolidine cores (Figure ).…”
mentioning
confidence: 99%
“…However, despite the past decade of great progress in enantioselective phosphonium salt catalysis, analogous P-based phosphonium salt catalysts by taking peptide residues as secondary active sites are very limited. Recently, Zhao and co-workers pioneered the development of bifunctional phosphonium salt catalysts derived from amino acids , and further demonstrated their effectiveness in a number of catalytic reactions . Very recently, we developed an l -threonine-derived bifunctional phosphonium salt catalyst for the highly enantioselective synthesis of tetrasubstituted aziridines. It should be noted that such an amino acid derived phosphonium salt possesses remarkably high tunability, and further, this catalyst with an ion-pairing moiety and peptide backbone that captures essential features of enzymatic active sites with hydrogen-donating characteristics becomes a multifunctional phase-transfer catalyst, which can be advantageous for asymmetric induction .…”
mentioning
confidence: 99%